Work and education in Karl Marx: the contradiction of intellectual and manual labor in the educational process (Research, Society and Development, 2020)
The aim of this paper is to understand the relationship between work and education in Marxist thought, especially from the intellectual and manual division of labor. The research is theoretical and seeks to develop an analysis of the categories work and education in the writings of Karl Marx, so the research method is the Marxist dialectical method. The work does not focus on a specific literature of Marx, because the theme is diluted in its various texts, requiring the reading of some of his works and even other Marxists who contributed to the theory. The centrality in Marx's thought is work, which in turn is an educational process. Work in Marxist theory is a fundamental condition for the constitution of being as a social being. It seeks to understand and define education in the field of fighting classes. It is the institution by which the ruling class conveys their ideologies. However, dialectically education can make a very significant contribution to the process of liberation and class organization of the oppressed.